2020
DOI: 10.3390/f11070760
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Cutting Mechanism of Oil Tree Peony Stem

Abstract: Tree peony is a deciduous shrub endemic to China, and peony seed oil (PSO) is an important plant oil resource. However, at present, pruning and fruits harvesting of oil tree peony are mainly completed by manual work, which has seriously affected production efficiency. By the need to develop efficient pruning and harvesting equipment for oil tree peony, this study investigated the effect of cutting tool geometric parameters and cutting speed on cutting force and energy. A cutting device was set up, and six cutt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…BOYDAŞ et al [16] reported that shearing force values of sainfoin stems obtained at an oblique angle of 28 • were lower than those at an oblique angle of 0 • . Similar results were reported by Yore et al [17] for rice straw, by Allameh and Alizadeh, [18] for rice stems, by Ghahraei et al [19] for kenaf stems and by Liu et al [20] for peony stems. The proper design of the cutting equipment can maintain the quality of the harvested product while minimizing the force and energy needed to accomplish the task.…”
Section: Resultssupporting
confidence: 89%
“…BOYDAŞ et al [16] reported that shearing force values of sainfoin stems obtained at an oblique angle of 28 • were lower than those at an oblique angle of 0 • . Similar results were reported by Yore et al [17] for rice straw, by Allameh and Alizadeh, [18] for rice stems, by Ghahraei et al [19] for kenaf stems and by Liu et al [20] for peony stems. The proper design of the cutting equipment can maintain the quality of the harvested product while minimizing the force and energy needed to accomplish the task.…”
Section: Resultssupporting
confidence: 89%
“…Tree peony is a perennial woody deciduous shrub, belonging to the family Paeoniaceae , section Moutan, and genus Paeonia , 1 and it has been renowned for its large flowers, diverse flower color, graceful appearance, and strong fragrance. 2 , 3 Tree peony has a long history of ornamental cultivation, and with long-term natural and artificial selection, there are more than 2000 varieties that vary in flowering traits of tree peony worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Since the tool is subjected to a positive pressure perpendicular to the edge and a lateral force parallel to the edge when cutting the branch, the relative slip between the branch and the edge increases when the slip cutting angle increases, thus enhancing the cutting action of the edge on the branch and reducing the peak cutting force (Figure 13). In contrast, during unsupported cutting, the trend of reduction of peak cutting force is relatively flat due to the relatively small trend of variation of chipping angle with tool wedge angle [37].…”
Section: Effect Of Slip Cutting Angle On Peak Cutting Forcementioning
confidence: 92%
“…From the slip-cutting theory [20,36], it is known that when the slip cutting angle is greater than 20 • , branches will produce the phenomenon of external slip, so the slip cutting angle is set to 5 • , 10 • , 15 • and 20 • in the single-factor experiment of tool slip cutting angle for a total of four levels; when the other groups of single-factor tests are conducted, the slip-cutting angle is taken as 20 • to ensure that the minimum cutting force is obtained. Comprehensive consideration of the wedge edge strength and blade life will be the relationship between the tool wedge angle singlefactor experiment wedge angle set to 20 • , 25 • , 30 • , 35 • -a total of four levels [37,38]; when conducting the other single-factor test, the wedge angle was 25 • . Referring to previous studies [3,19], the cutting gap was set from 0.1 to 3 mm and set to four levels in the singlefactor test of cutting gap; when conducting other group tests, the cutting gap is taken as 1 mm.…”
Section: Experimental Factorsmentioning
confidence: 99%